2007
DOI: 10.1089/jmf.2005.066
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Effects of Chopped Garlic in Ground Beef and Raw Meatball (Çiğ Köfte)

Abstract: This study was carried out to investigate the antimicrobial effects of chopped garlic in ground beef and raw meatball (çig köfte), which is a traditional food product eaten raw. Fresh minced ground beef and raw meatball batter prepared with traditional methods were separated into groups. Chopped and crushed garlic was added to each batch in order to reach various concentrations from 0% to 10%. The ground beef samples were stored at refrigerator and ambient temperatures. The raw meatball samples were only store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…It would be speculated that Yoghurt or YS addition to the cig kofte may have been inhibit the growth of S. aureus and yeast. Similarly, Aydin et al (2007) reported that 5% and 10% of garlic added to cig kofte decreased yeast and mould counts. Additionally, S. aureus may be found in cig kofte as a contaminant depending on personal hygiene.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It would be speculated that Yoghurt or YS addition to the cig kofte may have been inhibit the growth of S. aureus and yeast. Similarly, Aydin et al (2007) reported that 5% and 10% of garlic added to cig kofte decreased yeast and mould counts. Additionally, S. aureus may be found in cig kofte as a contaminant depending on personal hygiene.…”
Section: Resultsmentioning
confidence: 93%
“…The differences among the TAMB counts of the samples during the storage period were also statistically significant (P<0.05) ( Table 2). In another study, Aydin et al (2007) reported that 5% and 10% of garlic added to formulation decreased the TAMB counts of the cig kofte. Therefore, some bioactive components of the additives e.g.…”
Section: Resultsmentioning
confidence: 93%
“…However, our preliminary study indicated that higher concentrations of garlic and onion resulted in reduced sensory quality of meat (data not shown in a tabular form). Aydin et al (2007) reported that chopped garlic inhibited the microbial growth in ground beef depending on the garlic concentration, but the effect was still minimal even at the highest concentration (10%).…”
Section: Microbiological Qualitymentioning
confidence: 99%
“…Due to their high antimicrobial activities, both garlic and onion can be used as natural preservatives to control microbial growth in various food products (Pszczola, 2002). Previous studies on the addition of garlic in ground beef revealed that it could minimize lipid oxidation and enhance the color and microbial safety of the meat (Aydin et al, 2007;Gupta and Ravishankar, 2005;Yin and Cheng, 2003). The effect of irradiation on fresh meat has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…On week 8; psychrotrophic bacteria count increased to 4.78 log cfu/g and 4.66 log cfu/g for anchovy and mussel pastes, respectively. Enterobactericeae and coliform bacteria could not be isolated throughout the period of fermentation for two groups due to slowing-down effect on microbiological growth of chopped garlic depending on the garlic concentration, along with some other spices such as black and red pepper [18,19]. Yeast and mould counts of anchovy and mussel pastes ranged between 2.58 log cfu/g (week 2, anchovy paste) and 1 >log cfu/g.…”
Section: Microbiological Analysismentioning
confidence: 99%